Socio-economic inequalities in the rate of stillbirths: a population based study. (7th June 2011) - Seaton, S E; Smith, L K; Draper, E S; Manktelow, B N; Springett, A; Field, D J
Abstract : To investigate socioeconomic inequalities in stillbirth rates in England national population data were used on all singleton stillbirths 1997–2007. Causes of stillbirth were coded according to the extended Wigglesworth classification and denominator data were the total number of live births and stillbirths. Deprivation was measured using a small area level deprivation index. Poisson regression models were used to estimate the relative and absolute deprivation gap (comparing the most deprived tenth with the least deprived tenth) in rates of stillbirths (both all cause and by specific cause). In the most deprived decile, the overall rate of stillbirths was double that in the least deprived areas (Rate Ratio (RR): 2.06 (95% CI: 1.98 to 2.13)). Over the time period there has been a general widening of the deprivation gap (1997–1999: RR: 1.96 (95% CI: 1.83 to 2.11) 2005–2007: RR: 2.12 (95% CI: 1.95 to 2.31)). A similar pattern was seen for most individual causes. The widest deprivation gap in stillbirth rates was in congenital anomalies (RR: 3 (95% CI: 2.63 to 3.43) and antepartum stillbirths which were small for gestational age (RR: 2.41 (95% CI: 2.25 to 2.58)). Only 30% of the deprivation gap was explained by known causes such as congenital anomalies and intrapartum events. This leaves 70% of the gap accounted for by antepartum stillbirths of unknown cause. Further research is needed to understand these unexplained deaths.